Comercialización y rentabilidad de las distribuidoras de maíz y su relación con la economía del cantón La Maná, provincia de Cotopaxi año 2011 - Pérez Proaño, Jessica Johanna (2015)
The present investigation established the marketing and profitability generated in large, medium and small distributors of corn and its relationship to the economy of La Maná canton in 2011, the bibliographic study focuses on the methodology of an economic - financial study of this sector, in gathering information was necessary the use the necessary techniques as the survey for consumers and owners of the distributors; through research it was possible to determine that all the companies don not have an adequate control of economic and financial management by the business owners, due to lack of accounting culture.